Sustainable safety practices and hazard management in the oil and gas industry: an HSE perspective - Jamil, Zara; Nordin, Shahrina; Miraj, Mohammad; Alqahtani, Mazen; Shaik, Riyaz Ahamad; Akhter, Shamim; Nizam Isha, Ahmad Shahrul (Frontiers in Public Health, 2025)
Despite advancements in operational technologies, the oil and gas (O&G) industry continues to face safety lapses due to persistent challenges in occupational health and safety management (OHSM), hazard identification and risk assessment (HIRA), and safety communication (SC). This study aims to examine how OHSM, HIRA, and SC influence safety knowledge (SK) and safety performance (SP), with safety culture (SCULT) mediating these relationships. A novel framework, integrating technical, procedural, and cultural dimensions is proposed and empirically tested. Grounded in social exchange theory (SET), this framework is distinct in its dual focus on system-level safety practices and cultural mechanisms in high-risk environments. Malaysia’s downstream O&G sector was chosen due to its operational complexity, multicultural workforce, and elevated accident rates, making it a critical context for evaluating sustainable safety interventions. Data was collected from 350 employees from the operational department using stratified sampling across two major national oil companies PGB and MLNG. Partial least squares structural equation modeling (PLS-SEM) was employed to validate the model, demonstrating strong reliability and predictive relevance (SRMR = 0.064, AVE > 0.5). Notably, SC exhibited weak direct effects on SK and SP, but strong indirect effects via SCULT, suggesting that communication-based safety interventions are only effective when trust and cultural alignment are present. Behavioral outcomes such as proactive safety participation and cognitive outcomes such as hazard recognition were both positively influenced by a strong SCULT. This research offers practical strategies for industry stakeholders, including the adoption of a near-miss reporting system, behavior-based safety (BBS) training programs, and culturally adaptive communication audits. Policymakers are encouraged to embed cultural indicators within national safety audit frameworks and promote leadership accountability across organizational levels. The findings emphasize that achieving sustainable safety outcomes require more than structural compliance with culturally integrated safety systems.